A Novel MgO-CaO-SiO2 System for Fabricating Bone Scaffolds with Improved Overall Performance - Hang Sun (Materials, 2016)
Although forsterite (Mg2SiO4) possesses good biocompatibility and suitable mechanical properties, the insufficient bioactivity and degradability hinders its further application. In this study, a novel MgO-CaO-SiO2 system was developed by adding wollastonite (CaSiO3) into Mg2SiO4 to fabricate bone scaffolds via selective laser sintering (SLS). The apatite-forming ability and degradability of the scaffolds were enhanced because the degradation of CaSiO3 could form silanol groups, which could offer nucleation sites for apatite. Meanwhile, the mechanical properties of the scaffolds grew with increasing CaSiO3 to 20 wt %. It was explained that the liquid phase of CaSiO3 promoted the densification during sintering due to its low melting point. With the further increase in CaSiO3, the mechanical properties decreased due to the formation of the continuous filling phase. Furthermore, the scaffolds possessed a well-interconnected porous structure and exhibited an ability to support cell adhesion and proliferation.